The physical activity and social support scale: a translation and psychometric validation study in a Chinese college student sample - Cao, Yunxia; Yuan, Junfeng; Luo, Lin (Frontiers in Psychology, 2024)
Objective This study aims to evaluate the reliability and validity of the Chinese version of the Physical Activity Social Support Scale (PASSS-C) and its measurement invariance across different gender groups in a Chinese college student sample. Methods A total of 1,689 Chinese college students participated in the study. We assessed the internal consistency of PASSS-C using Cronbach’s alpha and McDonald’s omega. A Confirmatory Factor Analysis (CFA) was conducted to test its five-factor model. Multi-group CFA was used to examine measurement equivalence between male and female groups. Convergent and criterion-related validity were assessed using Pearson correlation coefficients. Results The overall internal consistency of PASSS-C was good with a Cronbach’s alpha of 0.952, and the subscales showed acceptable consistency. The CFA results supported the five-factor structure of PASSS-C in the college student sample, with values of CFI = 0.932, TLI = 0.917, RMSEA = 0.048, 90% CI [0.043 0.053], SRMR = 0.047. Scalar invariance was also supported across different gender groups, with ΔCFI = −0.003, ΔTLI = 0, ΔRMSEA = 0. PASSS-C demonstrated good convergent and criterion-related validity. Conclusion PASSS-C exhibits satisfactory psychometric properties and is a valid and reliable tool for assessing the perceived level of social support for physical activity among college students.